The condition of Polish economy in the first years after regaining independence. Political and legal outline - Tomasz Chłopecki (Facta Simonidis)
The goal of this thesis was to synthetically present social and economic ideas in the first years after regaining independence by Poland. Economic concepts, tendencies and plans treated in general lines undoubtedly aimed at changing existing social and economic relations. Three elements must be taken into consideration while assessing economic achievements of the Second Polish Republic in the first years after regaining independence: firstly, the condition of Poland on November 11, 1918, after one hundred and twenty-three years of bondage and damage caused by the First World War; secondly, the time in which changes were made, and thirdly, financial means that Poland possessed, particularly external aid – especially in a form of foreign loans.